Value Сhanges in Contemporary Emigrant Literature: To Have or to Be? - Laurušaitė, Laura (Colloquia, 2018)
The author of the article, based on the method of imagological analysis, discusses the competing scenarios of a contemporary person’s existence – to have and to be, which emerge in their especially relevant forms in the contemporary prose by Lithuanian and Latvian emigrants. The prevailing economic causes of emigration determine the predominance of having in the contemporary emigration literature. Consumption as an impetus for happiness is more typical of former societies of lack, who do not yet understand the imagological nature of such happiness – the illusiveness of possessing. In the social structure of the host countries, Lithuanian and Latvian emigrants are usually the disadvantaged class, and therefore their desire to flaunt externally, to demonstrate their superiority by externals, is eminently obvious. They strengthen their symbolic power and self-realization by displaying themselves wearing demonstrative emblems in the form of expensive items, cars, and bright makeup. The article identifies other contemporary changes of values that have emerged in the literature written by emigrants: the shredded concept of freedom, loss of dignity and self-worth for the sake of money, and imperatives of bondage (dog imagotopics). The tendencies of such behavior (distorted conception of power, dominance, prestige, dignity, and freedom) unveil the general common problems of post-Soviet societies, revealing the erosion of existence, the distorted values, and sometimes the reverse of these two social forms, when possessing finds itself in the place of being. The new egoistical ideals of freedom, which contemporary emigrants cling to, testify to endangered social thinking, the weakening of the national mentality, and the entrenching self-centeredness. The model of being, which is alternative to having, is less frequent in the narratives of emigration, and usually manifests itself as a companion of academic emigration. The paradigm of being focuses on cultural rather than material or physical property, as well as on active self-realization and inner personal development.